Depigmented skin and phantom color measurements for realistic prostheses. Issue 1 (10th June 2013) - Tanner, Paul; Leachman, Sancy; Boucher, Kenneth; Ozçelik, Tunçer Burak
<x xml:space="preserve">Abstract</x> Purpose The purpose of this study was to test the hypothesis that regardless of human skin phototype, areas of depigmented skin, as seen in vitiligo, are optically indistinguishable among skin phototypes. The average of the depigmented skin measurements can be used to develop the base color of realistic prostheses. Methods and Materials Data was analyzed from 20 of 32 recruited vitiligo study participants. Diffuse reflectance spectroscopy measurements were made from depigmented skin and adjacent pigmented skin, then compared with 66 pigmented polydimethylsiloxane phantoms to determine pigment concentrations in turbid media for making realistic facial prostheses. Results The Area Under spectral intensity Curve (AUC) was calculated for average spectroscopy measurements of pigmented sites in relation to skin phototype (P = 0.0505) and depigmented skin in relation to skin phototype (P = 0.59). No significant relationship exists between skin phototypes and depigmented skin spectroscopy measurements. The average of the depigmented skin measurements (AUC 19, 129) was the closest match to phantom 6.4 (AUC 19, 162). Conclusion Areas of depigmented skin are visibly indistinguishable per skin phototype, yet spectrometry shows that depigmented skin measurements varied and were unrelated to skin phototype. Possible sources of optical variation of depigmented skin include age, body site, blood flow, quantity/quality of collagen, and other chromophores. The average of all depigmented skin measurements can be used to derive the pigment composition and concentration for realistic facial prostheses.